Green hydrogen Production from the oxidative reform of clean biogas over Ni/MgO-Nb2O5 catalysts (JSSE - Journal of Science & Sustainable Engineering, 2023)
Synthesis gas has a variety of applications ranging from its transformation into Fischer-Tropsch fuels, its processing to produce pure hydrogen, and even its direct combustion to generate energy, among many other applications. The objective of this work was the conversion of a model of biogas (clean biogas) into synthesis gas, H2 /CO, through oxidative reforming of methane over NiO/MgO/Nb2O5 catalysts. The catalysts in this work were prepared by impregnation and calcination (at 750ºC) and subsequently characterized by Energy Dispersive X-ray spectroscopy (EDX), Scanning Electron Microscopy (SEM), X-ray diffraction (XRD), Nitrogen Adsorption-Desorption (BET method) and Temperature Programmed Reduction with H2 (TPR). Finally, these catalysts were tested in the oxidative reform of methane (molar ratio of 1.5CH4:1CO2:0.25O2) at 750 ºC, 100mg of catalyst at a total flow of  110 mL.min-1, and 1 atm (inside the reactor). According to the results, it was verified that the catalyst composed of the NiO/MgO mixture is composed of the NiO-MgO solid solution, whereas the NiO/MgO/Nb2O5 catalysts are also formed by nickel niobate (NiNb2O6). All catalysts showed catalytic activity in the oxidative form of biogas,  NiMg, Ni60NbMg, and Ni40NbMg catalysts showed the highest conversion value. The efficiency of the catalysts in the oxidative reforming of biogas improved gradually as the %MgO increased in the NiO/MgO/Nb2O5 system. The characterization of the catalyst after the reaction demonstrated that the carbon formed is of the filamentous type.